Gerakan Dasar Felidae Dalam Animasi 2 Dimensi - Niky Hardinata; M. Suyanto - Universitas AMIKOM Yogyakarta; Sukoco - Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
Abstract – Animation literally means live / move. Supported by a variety of features and the existing methods make the animators are required to be able to work faster than ever before. Inverse kinematic methods is a method allowing the animator can create model of the movement more quickly because without requiring a lot of different images of a character for each frame. “A Felidae Basic Movements In 2 Dimensional Animation” is a study that aims to generate a model of the movement library of felidae animals in 2-dimensional animation that can be applied to to other felidae animal characters automatically and determine the degree of freedom of the joints on the felidae animal characters in a 2 dimensional animation. Limitation of the study variable is the method used is the method of inverse kinematics, felidae animals used are cheetahs, lions and cats, measuring the degree of joints done on a cat as a felidae animal model and a model of the movement created with Toon Boom Studio software. The method of analysis in this research is using research and development.Results of this research is data angle of freedom (degree of freedom) felidae animal joints to be implemented in 2 dimensional animation and walking and running model of the movement library of felidae animals (cheetahs, lions and cats) in a 2 dimensional animation that can be applied to the other felidae animal characters (cheetahs, lions and cats) automatically.The conclusion of the study is inverse kinematic methods can be applied in the manufacture of walking and running model of the movement felidae animals, felidae animal model of the movement libraries that have been made can be applied to other animal characters Felidae automatically.Keyword: Felidae, Inverse Kinematic, Degree of Freedom, Animation, Toon Boom Abstrak – Animasi secara harfiah berarti hidup/bergerak. Didukung oleh berbagai fitur dan metode yang ada membuat para animator diharuskan untuk bisa bekerja lebih cepat dari sebelumnya. Metode inverse kinematik merupakan metode memungkinkan animator bisa membuat model gerakan lebih cepat karena tanpa harus memerlukan banyak gambar yang berbeda-beda dari sebuah karakter untuk setiap frame.“Gerakan Dasar Felidae dalam Animasi 2 Dimensi” merupakan penelitian yang bertujuan untuk menghasilkan library model gerakan hewan felidae dalam animasi 2 dimensi yang bisa diterapkan pada karakter hewan felidae lainnya secara otomatis dan mengetahui derajat kebebasan sendi-sendi pada karakter hewan felidae dalam animasi 2 dimensi. Batasan variabel penelitian adalah metode yang digunakan yaitu metode inverse kinematik, hewan felidae yang dipakai yaitu cheetah, singa dan kucing, pengukuran derajat sendi dilakukan pada kucing sebagai model dari hewan felidae dan model gerakan dibuat dengan software Toon Boom Studio. Metode analisis dalam penelitian ini adalah metode research and development.Hasil dari penelitian ini adalah data sudut kebebasan (degree of freedom) sendi hewan felidae untuk diterapkan dalam animasi 2 dimensi dan library model gerakan berjalan dan berlari hewan felidae (cheetah, singa, dan kucing) dalam animasi 2 dimensi yang bisa diterapkan pada karakter hewan felidae (cheetah, singa, dan kucing) lainnya secara otomatis.Kesimpulan dari penelitian ini adalah metode inverse kinematik dapat diterapkan dalam pembuatan model gerakan berjalan dan berlari hewan felidae, library model gerakan hewan felidae yang sudah dibuat dapat diterapkan pada karakter hewan felidae yang lainnya secara otomatis.Kata kunci: Felidae, Inverse Kinematik, Degree of Freedom, Animasi, Toon Boom